Legal Regime and Financial Reporting Quality1. (25th August 2014) - Filip, Andrei; Labelle, Réal; Rousseau, Stéphane
Abstract This article uses the Canadian environment, where French civil law (FCL) in the province of Quebec coexists with common law (CL) in the Rest of Canada (denoted as bijural), to test the thesis of the neutrality of the legal system with regard to financial reporting quality (FRQ). This single‐country design allows for a better control over other factors that influence FRQ. The FCL environment appears to encourage firms to publish accounting data of better quality due to the greater liability risk faced by auditors and corporate directors under that regime. These findings, based on 10 years of data and seven attributes of FRQ, are robust to different matching procedures and model specifications. This research contributes to the current debates in Canada as to whether financial market regulation under FCL and CL jurisdictions should be unified under a single CL national securities regulator. At the broader level, the results support claims that a more in‐depth understanding of the implementation of civil law and CL is needed rather than gross generalization about the two systems. These results especially call into question that CL regimes are unambiguously superior to civil law regimes in encouraging high‐quality financial reports.